Acute phase proteins in bovine mastitis - SINGH, S V; PACHAURI, S P (The Indian Journal of Animal Sciences, 2014)
Evaluation of status of plasma glycoproteins, classed as acute phase proteins, viz. haptoglobin,Â fibrinogen, ceruloplasmin, Î±1 antitrypsin and albumin in mastitic cows compared to healthy ones. was done. The plasma concentration of haptoglobin, fibrinogen, Î±1 antitrypsin and ceruloplasmin was significantly higher and of albumin significantly lower in mastitic cows. The relative changes in plasma acute phase proteins may serve as diagnostic markers in bovine mastitis.